ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA SISWA DI SMK KOTA MAKASSAR - Fachrum Firdaus; Purnamawati; Abdul Muis Mappalotteng (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study seeks knowledge about the interest in entrepreneurship of SMK students in Makassar City with several variables namely: 1) How is the level of entrepreneurial knowledge on students' interest in entrepreneurship, 2) How does the family environment affect students' interest in entrepreneurship, 3) Does the entrepreneurial spirit of students affect students' entrepreneurial interest, 4) Does self-efficacy affect students' entrepreneurial interest. The type of research used is quantitative. With the research sample consisting of students who have received PKK subjects (creative products and entrepreneurship), and have carried out industrial work practices. Data collection techniques using a questionnaire (questionnaire) and documentation. The results of the study are (1) for the level of students' entrepreneurial knowledge on learning interest has results that are not positive in their influence, (2) there is a positive influence between the family environment and students' interest in entrepreneurship, (3) there is a positive influence between students' entrepreneurial spirit and interest in entrepreneurship, (4) there is a positive influence for self-efficacy and students' interest in entrepreneurship